구강암의 발생현황과 원인 - 한지형; Ji Hyoung Han; 김응권; Eung Kwon Kim; 임순환; Soon Hwan Lim; 김창희; Chang Hee Kim (Chiwisaeng gwahakoeji, 2012)
The purpose of this study was to examine pervasive trends in oral cancer in different countries in an effort to discuss what to do to prevent cancer and drop a death rate. The materials of the study were selected from among articles of oral cancer by searching risk factor and epidemiology at a website (www.oraloncology.com). As a result of analyzing the selected literature, it``s found that in our country, the percentage of oral cancer in total cancer dropped but the number of oral cancer patients was on the rise every year. In foreign countries, the number of oral cancer patients was on the increase as well, whereas the lethality dropped. In terms of demographic characteristics, the incidence rate of oral cancer was higher among men than women overall. The incidence rate of oral cancer was larger among older people. The major causes of oral cancer were smoking and drinking. To reduce the incidence rate of oral cancer, every possible institutional, administrative and legal measure should be taken to ensure of anti-smoking policies, and publicity of moderation in and abstinence from drinking should be reinforced. The additional causes of oral cancer were demographic characteristics by country and region. The incidence of oral cancer was under the influence of that was affected when the level of personal economy and education was low. Therefore it``s important to redress social imbalance within a country and among countries to remove socioeconomic divide. As the oral cancer patients has increased every year, the incidence rate of it should accurately be grasped, and sustained research efforts should be made in consideration of demographic characteristics. Early diagnosis, public oral health education and preventive policies are all required to decrease the incidence rate of oral cancer.